Brief Research Report: Expression of PD-1 and CTLA-4 in T Lymphocytes and Their Relationship With the Periparturient Period and the Endometrial Cytology of Dairy Cows During the Postpartum Period - Souza, Carolina Menezes Suassuna de; Lima, Ewerton de Souza; Ordonho, Raphael Ferreira; Oliveira, Bianca Rafaella Rodrigues dos Santos; Rodrigues, Rebeca Cordeiro; Moura, Marquiliano Farias de; Lima, Daniel Magalhães; Blagitz, Maiara Garcia; Ramos Sanchez, Eduardo Milton; Medeiros, Isac Almeida de; Souza, Fernando Nogueira; Fernandes, Artur Cezar de Carvalho (Frontiers in Veterinary Science, 2022)
The present study evaluated the expression of PD-1 and CTLA-4 in blood T lymphocytes during the periparturient period and their relationship with uterine health in dairy cows, as determined by endometrial cytology and serum concentrations of β-hydroxybutyrate (BHB) and nonesterified fatty acids (NEFAs). The second objective of this study was to investigate whether the expression of PD-1 and CTLA-4 in T lymphocytes is associated with the serum acute phase-protein haptoglobin concentration during the periparturient period. In the present study, we observed higher expression of CTLA-4 and PD-1 in T lymphocytes at parturition and in the prepartum period, which could indicate a relationship between these immune checkpoints and immunological tolerance during gestation in dairy cattle. In addition, a negative association between the expression of these immune checkpoints prepartum or at parturition and endometrial cytology at T20 and T30 was observed, indicating the negative implications of these immune response regulators in susceptibility to infections. This finding was further corroborated by the relationship between the serum concentration of haptoglobin and the expression of CTLA-4 and PD-1 by T lymphocytes. However, we did not observe a relationship between the indicators of negative energy balance, evaluated by the serum concentrations of BHB and NEFA, and the expression of the immune checkpoint markers studied. Thus, our findings represent an initial step that paves the way for the development of new therapeutic alternatives directed by the host with the objective of increasing the resistance of dairy cattle to infections in this critical period of life.